Tinjauan Kriminologis Tindak Pidana Pembunuhan Berencana Oleh Suami Terhadap Istri - Nusu, Muhammad Ikhsan; Putera, Airlangga (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2023)
The development of this modern era, many crimes happen outside human reason, the crime rate of criminal acts everyday seems to never run out, even crimes happen the more increase on society. In 2020 there was a criminal case of premeditated murder by a husband againts his wife which causes the victim to be disabled for life. In criminal law its regulated in article 339 and 340 of criminal code article about murder and prmeditated of murder. The author’s aim is to make this a form of understand the factors of occurance a criminal case of premeditated murder and how to prevent a criminal case of premeditated murder. and added again less of attention from relatives of both and socialization from neighbor so that’s making crimes of murder and prmeditated of murder this happen. factors of occurance a criminal case of premeditated murder is heartache factor, treason factor, economic factor, low level of education and social environment. Preventif, repressive, and currative is prevent a criminal case of premeditated murder. Abstrak: Perkembangan zaman yang sudah modern ini banyak tindak pidana terjadi diluar nalar manusia. Angka kriminalitas tindak pidana setiap harinya seakan tiada pernah habis. Bahkan hingga kini, pada tahun 2020 kemarin terjadi kasus tindak pidana pembunuhan berencana oleh suami terhadap istri yang menyebabkan seorang istri menjadi korban. Dalam hukum pidana diatur pada pasal 338-340 KUHP. Tujuan penulis membuat ini sebagai bentuk untuk memahami faktor-faktor penyebab terjadinya tindak pidana pembunuhan berencana dan upaya pencegahan pembunuhan berencana. Faktor dendam (sakit hati), faktor perselingkuhan, faktor ekonomi, faktor kekerasan, rendahnya tingkat pendiddikan dan lingkungan pergaulan merupakan faktor penyebab terjadinya pembunuhan berencana. Adapun upaya preventif, upaya refresif dan upaya kuratif adalah upaya untuk mencegah terjadinya tindak pidana pembunuhan berencana.